2012
DOI: 10.1186/1756-0500-5-640
|View full text |Cite
|
Sign up to set email alerts
|

Non-high density lipoprotein cholesterol versus low density lipoprotein cholesterol as a discriminating factor for myocardial infarction

Abstract: BackgroundSerum total cholesterol (TC) and LDL cholesterol (LDL-C) have been used as major laboratory measures in clinical practice to assess cardiovascular risk in the general population and disease management as well as prognosis in patients. However, some studies have also reported the use of non-HDL cholesterol (non-HDL-C). As non-HDL-C can be calculated by subtracting HDL-C from TC, both of which do not require fasting blood sample in contrast to LDL-C which requires fasting blood sample, we aimed to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Hence, the European Atherosclerosis Society consensus panel recommends elevated TG and low HDL-C as targets for treatment [25]. The association of HDL-C with myocardial infarction was found to be stronger than LDL-C in the study of Sigdel et al [26], possibly indicating that HDL-C could be the major determinant of clinical outcomes. The findings from the present study emphasize that HDL-C and TG should be given equal, if not more, importance than other routinely measured lipid parameters in the context of blood rheology and CVD.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, the European Atherosclerosis Society consensus panel recommends elevated TG and low HDL-C as targets for treatment [25]. The association of HDL-C with myocardial infarction was found to be stronger than LDL-C in the study of Sigdel et al [26], possibly indicating that HDL-C could be the major determinant of clinical outcomes. The findings from the present study emphasize that HDL-C and TG should be given equal, if not more, importance than other routinely measured lipid parameters in the context of blood rheology and CVD.…”
Section: Discussionmentioning
confidence: 97%
“…9 HDL-C is strongly associated with MI. 32 Because the association of HDL-C with incident HF was independent of interim MI in participants with diabetes, we speculated that alternative pathways possibly occurring before MI may play a greater role in this association. Insulin resistance is an independent predictor of HF, 25,33 but also has a role in the development of high triglyceride and low HDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that we have overestimated the prevalence of total hypertension and the prevalence of untreated hypertension based on this recent recommendation. Similarly, while the recommendations in the Third Report of the National Cholesterol Education Program Expert Panel on Detection, Evaluation and Treatment of High Cholesterol in Adults (ATP III) focus on total cholesterol with non‐HDL cholesterol as a secondary target, recent studies have found non‐HDL cholesterol to be an independent predictor of CVD risk .…”
Section: Discussionmentioning
confidence: 99%